An Improved Multi-Objective Particle Swarm Optimization Algorithm for Solving Multi-mode Resource-constrained Multi-project Scheduling Problem - Chen, Dejun; Wang, Ben (2023 4th International Conference on Information Science, Parallel and Distributed Systems (ISPDS), 2023)
To address the challenging Multi-Mode Resource-Constrained Multi-Project Scheduling Problem (MRCMPSP) that involves scheduling multiple instances of projects with various execution modes, subject to resource constraints and precedence relations, this paper proposes the Delay Parallel Decoupled Schedule Generation Scheme (DPDSGS) and the Dynamic-Cluster Dynamic-Weight Multi-Objective Particle Swarm Optimization (DCDW-MO-PSO) based on a dynamic topology structure. These methods can generate multi-project baseline schedules that meet practical requirements and optimize three objectives: total makespan (TMP), total project delay (TPD), and max project delay (MPD). Moreover, the superior optimization performance of DCDW-MO-PSO is demonstrated by comparing it with other multi-objective optimization algorithms using example problems.